Geopolitical Risk Transmission in Indonesia’s Financial and Commodity Markets - Raisa Dea Fitrasari; Sigit Surya Hariwibowo; Parlis Lawalata; Rachman Hadi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study investigates the impact of geopolitical risk on Indonesia’s macroeconomic stability using a Vector Autoregression (VAR) approach. Quarterly data from 2010 to 2025 are analyzed, encompassing geopolitical risk, economic growth, stock market index, inflation, interest rates, exchange rates, and commodity prices. The impulse response function results indicate that shocks from geopolitical risk exert limited and temporary effects on most macroeconomic variables, which generally return to equilibrium within a few periods. In contrast, financial variables, particularly stock prices and gold, exhibit more pronounced responses. Variance decomposition further demonstrates that the influence of geopolitical risk is relatively minor for real sector variables but more significant in financial markets. These findings suggest that Indonesia’s economy demonstrates considerable resilience to geopolitical shocks, with transmission occurring primarily through financial channels.